Media Modifikasi Tepung Ikan Teri, Rumput Laut, Ubi Jalar Ungu dapat Mempercepat Pertumbuhan Mycobacterium Tuberculosis - Rohmi Rohmi; Maruni Wiwin Diarti; Yunan Jiwintarum (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Tuberculosis (TB) is one of the infectious diseases which is still a health problem in Indonesia caused by M. Tuberculosis. The common growth medium used to growth M. Tuberculosis is Lowenstein-Jensen. Examination by culture method has several disadvantages: the incubation period is too long to calculate the growth of M. tuberculosis that reaches 8 weeks to be able to declare negative results. LJ medium is relatively expensive and requires special manufacture that requires precision. Objective to know the result of growth rate and growth rate of M. tuberculosis from combination formulation media of local food of sea fish meal (Stolephorus sp), Purple Sweet Potato flour (Ipomoea batatas) and Euchema Spinosum Seaweed flour called TURLM media (Grass Sweet Teri Sea Medium). The method of this research is this research is an exploratory research in laboratory, using three forms of TURLM media formulation and Loweinstein-Jensen media comparator, data collected in the form of growth speed and fertility rate of M. tuberculosis, descriptive data analysis. The results showed that TRULM media formulas 1,2 and 3 can show the growth of M. Tuberculosis coloccus of ATCC 25177, with the best growth rate in TURLM Formula 3 medium which is similar to LJ control media. Fertility growth rate of M. Tuberculosis ATCC 25177 TURLM medium The best formula is TRULM Formula 3 whose fertility rate is equal to growth in Loweinstein-Jensen (LJ) control media. The conclusion of this research is that TURLM formula 3 media can be used as growth media of M. tuberculosis which can accelerate the growth of M. Tuberculosis and show good fertility rate.